How do information problems constrain anticipating, mitigating, and responding to crises?. (15th October 2022) - Lentz, Erin C.; Maxwell, Daniel
Abstract: The explosion in data availability and new analytical tools combined with increasing humanitarian need and the imperative of anticipatory action compel us to rethink humanitarian information systems and humanitarian action for the future. Synthesizing interviews with humanitarian practitioners, donors, analysts, and researchers and analyses of early warning (EW) information systems and their linkages to Anticipatory Action (AA), we describe six information challenges within the current system: abundant but confusing information, the difficulty of predicting conflict, politicized information, limitations of new analytical tools, varying information needs, and limited data sharing. We then propose an approach to improve the timeliness and appropriateness of action for humanitarian crises and disasters. Rather than ask, "What can we do with the information (early warning and otherwise) that we have to inform action?" we propose asking, "What information do we need for anticipatory (and other) action?" In other words, we propose planning from known and likely hazards and actions back to information needs. Such an approach should help to mitigate shocks before they cause major humanitarian crises. While not all crises can be prevented, this approach could also support responsive action, which is equally important for protecting human life and dignity.